Are Indonesian new pictorial health warnings more effective than the old ones? - Jovian Philip Swatan; Firas Farisi Alkaff; William Putera Sukmajaya; Sulistiawati Sulistiawati; Azimatul Karimah (International Journal of Public Health Science (IJPHS), 2022)
Smoking remains as a nation-wide health problem in Indonesia. Several measures had been conducted to motivate smoking cessation, among those is the use of pictorial health warnings (PHWs). PHWs have been implemented since 2014, and some of the pictures were revised in 2018. However, there was no evaluation regarding the effectivity to this date. This study compared the effectivity of the old and new versions of PHWs in promoting smoking cessation. This was a cross-sectional study conducted in one of the sub-districts in East Java, Indonesia, in February 2020. Study population were local villagers aged at least 18 years who visited the sub-district’s primary healthcare during the study period. Consecutive sampling was used as the sampling method. Respondents were interviewed using a pre-determined questionnaire. The old and new versions of PHWs were printed and showed to the respondent during the interview. Comparison between groups was analyzed using McNemar test. A total of 103 respondents participated in this study. More respondents agreed that the old version of PHWs was considered more effective to motivate smoking cessation as compared to the newer version (71.84% vs 64.08%), although the significance was marginal (p=0.077). Our study showed that both versions of PHWs were considered effective to promote smoking cessation. However, more respondents agreed that the old version of PHWs were more effective than the new PHWs. We recommend policymaker to conduct a field study to test the effectivity of the proposed PHWs before revising the legal regulation in the future.